ROLE OF THE CULTURAL SECTOR IN ENHANCING ECONOMIC PERFORMANCE: A STATISTICAL STUDY OF THE EUROPEAN UNION COUNTRIES BOUDJEMAA - Mahdia, Boudjemaa; Souhir, Hamid (The journal of contemporary issues in business and government, 2024)
In this research paper, we sought to address the issue centered on the economic role of the cultural sector. To answer this question, the study was divided into two main sections. The first section deals with the historical development of the cultural economy, while the second presents statistics on the contribution of the European Union's cultural sector to job creation and the relationship between the added value of the cultural sector and the economic growth rate of the European Union. The research concluded that the cultural sector has a moderate contribution to enhancing economic growth rates and in creating jobs.